Do COVID-19 Worries, Resilience and Emotional Distress Influence Life Satisfaction? Outcomes in Adolescents in Ecuador during the Pandemic: SEM vs. QCA - Juan Sebastián Herrera; Laura Lacomba-Trejo; Selene Valero-Moreno; Inmaculada Montoya-Castilla; Marián Pérez-Marín (MDPI AG, 2022)
COVID-19 and the measures adopted have been a problem for society at all levels. The aim of the study was to analyze the main predictors of life satisfaction among adolescents in Ecuador during the COVID-19 pandemic. Participants were 902 adolescents from Ecuador aged between 12 and 18 years (M = 15.30; SD = 1.28). Variables such as life satisfaction, resilience, emotional symptomatology, and worries about COVID-19 were assessed. Two statistical methodologies were compared (structural equation models (SEM) and qualitative comparative analysis (QCA)) to analyze the possible influence of worries about COVID-19, resilience and emotional symptomatology towards life satisfaction. The results indicated that in both models, worries about COVID-19 were negatively related to life satisfaction. However, having a greater worry, specifically for physical health issues, was associated with better life satisfaction. SEM models indicate that depression is negatively related to life satisfaction. In QCA models, high levels of life satisfaction are explained by low levels of anxiety and depression. Thus, resilience seems to play a mediating role in life satisfaction, although this is only true for the depression variable. It is necessary to detect signs of risk in this population and strengthen resilience in them as elements that can facilitate their adequate coping with their adverse situation.